Development of an eco-friendly UPLC method for simultaneous quantification of six selected phosphodiesterase-5 inhibitors and serotonin reuptake inhibitors in pharmaceutical formulations and adulterated food using a quality by design approach - Heba Abdel-Hafeez Mohamed; Mohamed Badawi NourEldin; Asmaa Ahmed El-Zaher; Sally Tarek Mahmoud (Future Journal of Pharmaceutical Sciences)
Abstract This study introduces an innovative, environmentally sustainable ultra-performance liquid chromatography (UPLC) method with UV detection for the concurrent quantification of six clinically relevant pharmaceuticals—vardenafil, avanafil, sildenafil, dapoxetine, duloxetine, and tadalafil—frequently employed in the management of erectile dysfunction and premature ejaculation. This study employs quality by design (QbD) concepts to optimize chromatographic settings, assuring good selectivity, precision, and resilience, while conforming to green analytical chemistry standards, in contrast to previously published approaches. A face-centered composite design was utilized to systematically optimize critical parameters, resulting in effective separation using a reversed-phase C18 column, an acetate buffer (pH 3), and a mobile phase composed of buffer and methanol (72.5:27.5, v/v) at a flow rate of 0.5 mL/min. The new approach exhibited significant sensitivity and robustness in pharmaceutical dosage forms and contaminated food samples, especially in identifying illicit sildenafil and tadalafil adulteration in honey-based products. The proposed approach was thoroughly validated in accordance with ICH principles, satisfying analytical performance criteria for linearity, precision, accuracy, and robustness. The method's environmental impact was assessed using AGREE metrics, validating its adherence to green analytical chemistry standards. This approach, characterized by its swift analysis time, low solvent usage, and exceptional separation efficiency, serves as a significant analytical instrument for quality control laboratories, pharmaceutical analysis, and food safety monitoring.